Hubungan Pengujian Cbr Metode Tumbukan Dengan Alat Uji Cbr Metode Tekanan Berdasarkan Uji Pemadatan Standard - Irwan, Devrisvansyah; Putra, Andius Dasa; Syah, Aminudin; Iswan, Iswan (Universitas Lampung, 2021)
The importance of soil as construction material needs to be considered carefully. With various soil conditions, a physical test is required to discover the characteristics of the soil and California Bearing Ratio (CBR) test in a laboratory to determine the bearing capacity of the basic land (subgrade). This research was conducted to assess the suitability of the CBR test value with two different compaction tools.The results of the CBR test with the collision method without immersion resulted in the design CBR value of 7.7% and the CBR value of the immersion sample of 3.6%. Meanwhile, the CBR test using a pressure modification device, the CBR values obtained in the samples not immersed at a pressure of 3 MPa, 6 MPa, 9 MPa, and 12 MPa, were 4.2%, 6.8%, 9.8%, and 11.4%. The CBR valuesfor the immersion samples were 2.95%, 4.2%, 4.45%, and 4.56%. The results obtained from the design CBR value of the pressure method with a pressure of 6MPa which is closest to the collision CBR value with a difference of 0.9% for no immersion and 0.6% for immersion. The assumption that the difference between the two methods is due to the compaction energy of 6 MPa strength is not the same as the energy produced from the use of hammer energy according to ASTM D 698, Test Method for Laboratory Compaction Characteristics.